In search of the best use of bags low-volume red blood cells concentrate. - Estácio, Adriana Guimarães; Brito Junior, Lacy Cardoso de (Medicina (Ribeirao Preto), 2021)
INTRODUCTION. The production of whole blood bags with a lower volume than expected is approved in the Consolidation Ordinance number 05/2017; however, its dispensation today takes into account only the hemoglobin and hematocrit content of the bag. OBJECTIVE. From the existing Brazilian technical parameters, determine the criteria for the best clinical use for low-volume red cell concentrate (LVRCC) bags produced at the HEMOPA Foundation. MATERIAL AND METHODS. We analyzed volume, hemoglobin content, and hematocrit of 525 LVRCC bags from double bags without addition of preservative; conventional triple bags with the addition of SAG-M (saline, adenine, glucose, and mannitol); triples bags top and bottom (TAB) with the addition of SAG-M, and quadruple bags TAB with “in line” filter and the addition of SAG-M. RESULTS. It was observed that 71.43% (375/525) of bags of LVRCC, regardless of bag type, were in conformance with hematocrit and hemoglobin content concerning Brazilian legislation. With the double and conventional triple bags, they had the highest values of hemoglobin content. It was also observed that the bags of whole blood collected with volumes between 350 and 404 mL generated LVRCC bags with the lowest rate of discard. The greatest discard of LVRCC bags occurred when the final volume ≤ 250 mL and hemoglobin ≤ 16 g/dL. CONCLUSION. It was observed that the best use of LVRCC bags occurred when the whole blood bags were between 350 and 404 mL and the LVRCC bags had a final volume ≥ 250 mL and hemoglobin ≥ 16 g/dL.